Exploring pre-university students’ construction of reasoned argumentation during computer - supported collaborative discussions using sequential analysis - Panir Selvam, Pavithra; Ma’rof, Aini Marina (Universiti Putra Malaysia Press, 2021)
The prominent role of reasoning skills in predicting academic outcomes is clearly evident over the years in that its inculcation in various face-to-face learning contexts has become progressively dominant, including in the collaborative learning (CL) settings. The pandemic crisis, however, challenged traditional learning approaches to shift to an online mode overnight resulting in dramatic changes of learning delivery whereby teaching is undertaken remotely and on digital platforms. Though impact of CL-based approaches in promoting reasoning skills have been well-documented over the years, a systematic analysis of learners’ behavioural patterns of argumentation and reasoning in a virtual collaborative learning environment is yet to be concretely established. The current study therefore sought to investigate the development of reasoned argumentation skills among pre- university students with mixed language abilities, using open-ending short stories via a computer-supported collaborative learning (CSCL) environment. Adopting the case study research design by applying a mixed-methods approach through both descriptive and sequential analyses, 12 pre-university students from a public research university served as participants of this study. The results show that language ability has a strong predictive factor on reasoned argumentation skills and there is an established tendency of the participants to produce constructive arguments over defensive or challenging viewpoints to alternative ideas. This calls for future studies to further investigate predictive factors of this tendency and to further ascertain the predictive role of language-rich discussions in facilitating various higher order thinking skills among learners.